Impact of medical cannabis legalisation: a thematic review - Ekmil Krisnawati Erlen Joni,; Shahrul Mizan Ismail,; Rohaida Nordin, (Penerbit Universiti Kebangsaan Malaysia, 2023)
The usage and values of cannabis, or cannabis for medicinal purposes, have been historically recognised since ancient times. Evidence from clinical research demonstrated the therapeutic advantages of cannabis in an extensively wide area of medicinal aspects. Resultantly, many nations have decided to legalise the medicinal use of cannabis. Despite the international recognition of medical cannabis, Malaysia maintains the status quo of cannabis prohibition as a highly addictive drug with no medicinal value. The Malaysian government argues that the harmful effects of medical cannabis legalisation outweigh the benefits. No review paper has discussed the current research patterns on the impact of medical cannabis legalisation, while thematic review studies on this issue are limited. Therefore, this article synthesised literature from 2017 to 2021 to identify research patterns and recent academic discussions on the impact of medical cannabis legalisation. A keyword search and screening process utilising Scopus and Web of Science (WoS) databases inclusion criteria yielded 718 peer-reviewed academic journal articles. Nonetheless, only 72 articles were selected for final evaluation following the exclusion and inclusion process. The thematic review of the 72 publications identified 19 preliminary codes on the impact of medical cannabis legalisation. The ATLAS.ti 9 software was utilised to conduct the theme analysis review of the selected articles. The quantitative results presented the research patterns of the impact of medical cannabis legalisation. Additionally, the qualitative analysis generated five main themes developed in the literature on the impact of medical cannabis legalisation, namely (1) impact on health, (2) impact on policy, (3) impact on society, (4) impact on health system, and (5) impact on criminal activities. The findings will benefit future studies on implementing medical cannabis law (MCL) in Malaysia. Unfortunately, this study is limited to Scopus and WoS databases, and the impact of recreational cannabis legalisation is not included. The findings may benefit future research on medical cannabis legalisation and the suitable regulatory framework of medical cannabis policy for Malaysia.